Proactive Approach to Containment of Enterovirus Infection in the Nursery. (July 2013) - Fuchs, Inbal; Golan, Agneta; Borer, Abraham; Shemer-Avni, Yonat; Dagan, Ron; Greenberg, David
Administration of prophylactic intravenous immunoglobulins to contacts of infants actively shedding enterovirus during a hospital nursery outbreak may attenuate severity of disease in those contacts and aid in containment of the outbreak. Four cases of neonatal enteroviral disease were treated in our hospital nursery in July and August 2011; 3 were presumed or proven vertical transmission cases and 1 was a presumed horizontal transmission. We aimed to prevent development of severe illness in contacts of affected neonates following a ministry of health advisory during the summer of 2011 warning of increased neonatal enteroviral morbidity and mortality in Israel. Strict infection control measures were implemented, including meticulous decontamination of the nursery environment and administration of intravenous immunoglobulin prophylaxis to contacts. No further horizontal transmission occurred after infection control interventions. Immunoglobulin prophylaxis to control enteroviral infection in the nursery should be considered as an auxiliary infection control intervention during a nursery outbreak.